"Dreams Don't Come True in Eritrea": Anomie and Family Disintegration due to the Structural Militarization of Society - Nicole Hirt (German Institute of Global and Area Studies (GIGA), 2010)
This article analyzes contemporary Eritrea's acute crisis within the framework of the theory of anomie. It is based on the hypothesis that militarization, forced labor, mass exodus, and family disintegration can be interpreted as the consequences of two incompatible norm and value systems: the collectivist, nationalistic, and militaristic worldview of the former liberation front and ruling party People's Front for Democracy and Justice (PFDJ), and the traditional cultural system of Eritrea's society. In 2002 the regime introduced an unlimited 'development campaign', thereby forcing large parts of the society to live as conscripts and perform unpaid labor. This has caused a mass exodus of young people and a rapid process of family disintegration. The article is based on empirical fieldwork and evaluates the ongoing developments, which have led to rapid economic decline and the destabilization of the entire fabric of society. – – 'In Eritrea werden keine Träume wahr': Anomie und Familiendesintegration als Folge der strukturellen Militarisierung der Gesellschaft. Im vorliegenden Artikel wird die akute Krise, die Eritrea erfasst hat, im Rahmen der Anomietheorie analysiert. Der Text basiert auf der Hypothese, dass Militarisierung, Zwangsarbeit, Massenexodus und Familiendesintegration als Folgen zweier inkompatibler Normen- und Wertesysteme interpretiert werden können: der kollektivistischen, nationalistischen und militaristischen Weltanschauung der ehemaligen Befreiungsfront und nun regierenden People's Front for Democracy and Justice (PFDJ) und der traditionellen Wertordnung der eritreischen Gesellschaft. Im Jahr 2002 rief das Regime eine zeitlich unbegrenzte 'Entwicklungskampagne' aus, die große Teile der Bevölkerung zu unbezahlter Zwangsarbeit als Rekruten zwingt. Dies verursachte einen Massenexodus der jüngeren Generation und zu einem rapiden Prozess der familiären Desintegration. Der Artikel basiert auf empirischer Feldforschung und analysiert die aktuellen Entwicklungen, die zu einem rapiden ökonomischen Niedergang und einer Gefährdung des gesamtgesellschaftlichen Zusammenhangs führten.
Keywords: 300; Eritrea; militarization; forced labor; family disintegration; mass exodus; anomie